Francophone Minority Communities: The Last Constitutional Standard-Bearers of Trudeau’s Language Regime - Richez, Emmanuelle (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2012)
The francophone and Acadian communities of Canada (hereinafter “FACC”) have until now been the primary constitutional standard-bearers of Pierre Elliott Trudeau’s constitutional language regime by promoting non-territorialized bilingualism through Charter-based judicial review. However, this regime is slowly being eroded by stealth and can no longer serve the interests of the FACC. This article first explains how minority language rights were the cornerstone of Trudeau’s political project and how an ideological interdependence developed between him and the FACC. Second, it describes the importance of the post-1982 institutional context in furthering the FACC’s constitutional objectives. Third, the article evaluates to which extent these objectives were fulfilled by conducting a general survey of the Supreme Court’s Charter jurisprudence in the area of francophone minority rights and its political consequences. It concludes that the FACC have exhausted the potential of Trudeau’s constitutional language regime and must now move beyond it, if they want to ensure their future well-being.